Competition in the Brain. The Contribution of EEG and fNIRS Modulation and Personality Effects in Social Ranking - Balconi, Michela; Vanutelli, Maria E. (Frontiers in Psychology, 2016)
In the present study the social ranking perception in competition was explored. Brain response (alpha band oscillations, EEG; hemodynamic activity, O2Hb) as well as self-perception of social ranking, cognitive performance, and personality trait (Behavioral Activation System, BAS) were considered during a competitive joint-action. Subjects were required to develop a strategy to obtain a better outcome than a competitor (C) (in term of error rate, ER, and response time, RT). A pre-feedback (without a specific feedback on the performance) and a post-feedback condition (which reinforced the improved performance) was provided. It was found that higher BAS participants responded in greater measure to perceived higher cognitive performance (post-feedback condition), with increased prefrontal left activity, perception of higher ranking and a better real performance (reduced RTs). These results were explained in term of increased sense of self-efficacy and social position, probably based on higher-BAS sensitivity to reinforcing condition. In addition, the hemispheric effect in favor of the left side characterized the competitive behavior, showing an imbalance for high-BAS in comparison to low-BAS in the case of a rewarding (post-feedback) context. Therefore, the present results confirmed the significance of BAS in modulating brain responsiveness, self-perceived social position and real performance during an inter-personal competitive action which is considered highly relevant for social status.